Anytime and Distributed Approaches for Graph Matching - Zeina Abu-Aisheh (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2016)
Due to the inherent genericity of graph-based representations, and thanks to the improvement of computer capacities, structural representations have become more and more popular in the field of Pattern Recognition (PR). In a graph-based representation, vertices and their attributes describe objects (or part of them) while edges represent interrelationships between the objects. Representing objects by graphs turns the problem of object comparison into graph matching (GM) where correspondences between vertices and edges of two graphs have to be found.